1983
DOI: 10.1093/ajcn/37.6.910
|View full text |Cite
|
Sign up to set email alerts
|

Fetal iron balance in the rat

Abstract: Maternal and fetal iron balance through pregnancy was examined in the rat. The 20th day was selected for detailed study because of the peak iron requirements at that time. The standard diet provided a borderline iron supply to the fetus due to the limited availability of its iron for absorption. When a more available form of iron was used, normal fetal development occurred over a range of dietary iron content from 16 to 2500 mg/kg. At a level of 5 to 8 mg/kg, there was attrition of placental tissues with frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…However, it is possibly associated with severe iron de®ciency itself. It has been reported (Finch et al, 1983) that low levels of plasma iron, as found in severe iron de®ciency, could result in damage to fetal tissues and reduced capacity of placental tissues to take up iron. Singla et al (1996) demonstrated that a mild degree of maternal anemia has little in¯uence on iron accretion in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possibly associated with severe iron de®ciency itself. It has been reported (Finch et al, 1983) that low levels of plasma iron, as found in severe iron de®ciency, could result in damage to fetal tissues and reduced capacity of placental tissues to take up iron. Singla et al (1996) demonstrated that a mild degree of maternal anemia has little in¯uence on iron accretion in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 wk on this diet, hemoglobin concentrations were determined and studies were performed only on rats with hemoglobin concentrations of less than 7 g/100 ml blood. Previously, we have shown that the low hemoglobin concentrations found in rats fed the low iron diet were accompanied by greatly lowered levels of plasma iron and increased total iron binding capacity and that the anemia was of a microcytic type (5,6,16). The control groups were fed the low iron diet during the experimental period, but received weekly intraperitoneal injections of 5 mg of iron in the form of iron dextran (Imferon, Merrell-National Labs).…”
Section: Methodsmentioning
confidence: 99%
“…After 6 wk on this diet, hemoglobin concentrations were determined and studies performed only on rats with hemoglobin concentrations of less than 7 g/100 ml blood. Previously, we have shown that the low hemoglobin concentrations found in rats fed the low iron diet were accompanied by greatly lowered levels of plasma iron and increased total iron binding capacity and that the anemia was of a microcytic type (4,5,14). The control groups were fed the low iron diet during the experimental period, but received weekly intraperitoneal injections of 5 mg of iron in the form of iron dextran (Imferon, MerrellNational Labs).…”
Section: Methodsmentioning
confidence: 99%